2017
DOI: 10.4183/aeb.2017.308
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Correlation with Bioclinical Benefits of Using Natural Therapeutic Factors in Knee Osteoarthritis

Abstract: Context and objective. The new insights in the pathogenesis of osteoarthritis (OA) reveal the implications of adipocytokines. This study aims to analyze the correlations between the serum value of adiponectin and the clinical rehabilitation effects in patients diagnosed with knee OA, admitted and treated in the complex balneal resort of Techirghiol lake. Subjects and methods. The prospective randomized clinical study included 23 patients in the study group, diagnosed with knee OA according to ACR criteria, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
(28 reference statements)
1
8
0
Order By: Relevance
“…Consistent with others, this study indicated that the observed hypoadiponectinemia in women with PCOS was related to hyperandrogenemia (24). Peloid treatment for osteoarthritis associated with obesity could improve adiponectin levels (28).…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with others, this study indicated that the observed hypoadiponectinemia in women with PCOS was related to hyperandrogenemia (24). Peloid treatment for osteoarthritis associated with obesity could improve adiponectin levels (28).…”
Section: Discussionsupporting
confidence: 89%
“…A future reference for balneal therapy will be taken into consideration once the acute flare stops. It is of interest to find if a correlation exists between the levels of serum adiponectin in this patient, previously and after balneal treatment, as we have the knowledge that adiponectine's levels in SLE are higher than normal (17) and that balneal therapy with cold mud applications also elevates adiponectine's level (18).…”
Section: Discussionmentioning
confidence: 96%
“…In the last years, balneological research was directed towards the study of specific inflammatory cytokines' involvement in musculoskeletal disorders. Correlations between peloid therapy and inflammatory pathways, at a molecular level, are established and new insights into the world of chondrocytes and osteoblasts are brought to light (85). Peat obtained from Taean-gun, Chungcheongnam-do, Korea, can be considered as a therapeutic option for pain relief of knee OA patients.…”
Section: Relevant Topical Data Regarding Mud Therapy In Physical and Rehabilitation Medicine (Prm) And Balneologymentioning
confidence: 99%